The Importance of ‘Likes’: The Interplay of Message Framing, Source, and Social Endorsement on Credibility Perceptions of Health Information on Facebook - Borah, Porismita; Xiao, Xizhu (Journal of health communication, 2018)
Online sources not only permeate the information-seeking environment of the younger generation, but also have profound influence in shaping their beliefs and behaviors. In this landscape, examining the factors responsible for credibility perceptions of online information is fundamental, particularly for health-related information. Using a 2 (frames: gain vs. loss) × 2 (source: expert vs. non-expert) × 2 (social endorsement: high vs. low) randomized between-subjects experimental design, this study examines the effect of health message framing and the moderating effects of social endorsement and source type on credibility perceptions of Facebook posts. Testing across two issues--physical activity and alcohol consumption--findings indicate that the gain-framed message was perceived as most credible. Additionally, significant three-way interactions suggest that social endorsement and source type affect the relationship between message framing and credibility perceptions. Specifically, the findings demonstrate that a gain-framed message from an expert source with high number of 'likes' is considered the most credible message. These findings have significant implications for information gathering from social media sources, such as the influence of 'likes' on health information.